2016
DOI: 10.1097/md.0000000000002725
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Ewing Sarcoma/Primitive Neuroectodermal Tumors in the Mediastinum

Abstract: Ewing sarcoma/primitive neuroectodermal tumors (ES/PNET) are high-grade malignant neoplasms. These malignancies present very rare tumors of thoracopulmonary area and even rarer in the mediastinum. In our knowledge, ES/PNET presented with multiple mediastinal masses has not been reported previously.We experienced a case of a 42-year-old man presented with gradual onset of left-side pleuritic chest pain. A contrast-enhanced chest computed tomography (CT) scan showed separate 2 large heterogeneously enhancing mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Malignant thymoma should be considered first when a large, irregular and uneven mass appears in the anterior mediastinum, which was the reason for misdiagnosis in the study. Malignant thymomas show similar radiologic findings as EWS ( 7 ). However, malignant thymomas are much less malignant than mediastinal ES, such as they usually have no lymph node metastasis and no pleural effusion.…”
Section: Discussionmentioning
confidence: 90%
“…Malignant thymoma should be considered first when a large, irregular and uneven mass appears in the anterior mediastinum, which was the reason for misdiagnosis in the study. Malignant thymomas show similar radiologic findings as EWS ( 7 ). However, malignant thymomas are much less malignant than mediastinal ES, such as they usually have no lymph node metastasis and no pleural effusion.…”
Section: Discussionmentioning
confidence: 90%
“…Extraskeletal occurrence of ES is rare; however, it can occur in any location [ 8 ]. Upon review of the medical literature, we identified cases reported in female and male genital organs such as the vulva, vagina, uterus, ovaries, and testicles [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common among these is the Ewing sarcoma/family of tumors (ES). As a mediastinal primary, ES is exceptionally rare in contrast to its more common thoracopulmonary location ( 63 , 64 ). Aspiration cytopathology consists of highly cellular smears with monotonous cells about 2–3 times the diameter of a mature lymphocyte dispersed individually with a minority in loose clusters.…”
Section: Diagnostic Categoriesmentioning
confidence: 99%